Near infrared spectroscopic assessment of engineered cartilage for implantation in a pre-clinical model - Jessica M. Falcon; Shital Kandel; William Querido; Justin Morman; Jay Patel; Liane M. Miller; Robert L. Mauck; Nancy Pleshko (Elsevier, 2022)
Introduction: Articular cartilage lacks the capacity for self-repair due to its relative avascularity. Regenerative medicine approaches are now widely investigated, but optimal solutions have not been identified. This is partially attributable to challenges in identifying appropriate engineered constructs for implantation, and in assessing the repair trajectory in pre-clinical models. Objective: We investigated non-destructive near-infrared (NIR) fiber optic spectroscopy-derived parameters to inform (1) identification of optimal tissue engineered cartilage constructs prior to implantation and (2) assessment of repair tissue composition in a Yucatan mini-pig chondral defect model. Methods: Tissue engineered cartilage (TEC) was developed using a co-culture system of bone marrow mesenchymal stem cells and chondrocytes encapsulated in a hyaluronic acid-based hydrogel. Near-infrared spectroscopy (NIRS)data were obtained from the TECs pre- and post-implantation and from repair tissue post-surgery. Healing response of the defects were compared to microfracture at 3 months post-implantation based on ICRS II scoring, mechanical testing, and NIRS. Results: No significant differences were found between the tissue engineered cartilage and microfracture repair tissue. Some NIR-determined properties of the developing TECs correlated significantly with aspects of the ICRS II repair tissue score, including the surface architecture and subchondral bone integration. Further, NIR-derived metrics to non-destructively assess repair tissue composition, in the presence of subchondral bone, were defined (5200/7000 cm−1 ratio), providing a valuable approach for future studies. Conclusion: Together, these data demonstrate the utility of NIR spectroscopy to identify developing TECs that may result in functional repair tissue and to facilitate repair tissue evaluation.